Zum Stand der Selbsthilfe in Deutschland – unter besonderer Berücksichtigung der Sucht-Selbsthilfe (European Journal of Mental Health, 2009)
The Present State of Self-Help in Germany – with Special Regard to Addiction Self-Help: This article presents the self-help scenery in Germany, which is unique in Europe. It deals with the dissemination of self-help groups and organisations, their various ways of proceedings, and their political influence. Different types of self-help groupings are described (12-steps-groups, psychologico-therapeutic talking-groups, and self-help organisations of chronically ill and handicapped persons). Special attention is given to self-help groups of addicted persons. In Germany only a small part of them are Alcoholics Anonymous. Beyond that a variety of other self-help groups devoted to abstinence of their members exist, in many cases attached to welfare organisations of the Catholic or Protestant Church. A specific factor in self-help groups for addicted persons is the possible recovery from the disease, which is not the case in self-help groups of chronically ill and handicapped persons. Finally the article presents some ideas about possible causes for the self-help movement, which developed over the last two or three decades, particularly in highly industrialised countries of Central, Western and Northern Europe. Some milestones along the German way to self-help are mentioned: the important role of research(ers), the support by state’s legislation, and finally the obligation of Germany’s statutory health insurance to support self-help financially.